Penerapan 5M dan Vaksinasi dalam Meningkatkan Kesadaran Diri Masyarakat Saat Pandemi Covid-19 di Kelurahan Sukorejo Kota Blitar - Winarto, Winarto; Risdiantoro, Rindra; Yordan, Adam; Mubarok, Muhammad Nanang (TAAWUN, 2022)
Vaccination or immunization aims to make a person’s immune system able to recognize and quickly fight bacteria or viruses that cause infection. The goal to be achieved by giving the COVID-19 vaccine is to reduce morbidity and mortality due to this virus. Although not 100% able to protect a person from Corona virus infection, this vaccine can reduce the possibility of severe symptoms and complications due to COVID-19. Efforts to prevent Covid-19 are to comply with health protocols. The purpose of this activity is to help Sukorejo Village in tackling the prevention of COVID-19. The method used is to educate the public on the importance of complying with health protocols and following vaccinations. The strategy used is to go directly to the community. The difficulty experienced is the community’s disobedience to the importance of maintaining 5M. The result of the activity is that there are students in the midst of the community, little by little the community is starting to become aware of the existence of Covid-19.